JOURNAL OF GOVERNMENT & POLITICS : Bureaucracy and the Politics of Identity : A Study on the Influence of Ethnicity on The Bureaucrat Recruitment Process in Sorong Selatan Regency, West Papua. - Bambang Purwoko (FISIPOL UMY, 2016)
Empirically, the central government of Indonesia introduced a uniform bureaucratic model to the entire territory of the country.